2016
DOI: 10.1080/19415257.2016.1258654
|View full text |Cite
|
Sign up to set email alerts
|

Closing the feedback loop: a productive interplay between practice-based research and school development through cross-professional collaboration in secondary education

Abstract: Closing the feedback loop: a productive interplay between practice-based research and school development through cross-professional collaboration in secondary education Schenke, W.; van Driel, J.H.; Geijsel, F.P.; Volman, M.L.L. : 10.1080/19415257.2016.1258654 Link to publication Published in: Professional Development in Education DOI General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
(48 reference statements)
0
15
0
1
Order By: Relevance
“…According to a review conducted by Zwart et al (2015), factors such as time, cooperation in research, ownership, a supportive work environment, coaching on inquiry-based working and access to resources influence teachers' engagement in inquiry-based working. Other studies have demonstrated the importance of school leaders in terms of encouraging inquiry-based working (Schenke 2015).…”
Section: Factors That Promote or Hinder Inquiry-based Workingmentioning
confidence: 99%
“…According to a review conducted by Zwart et al (2015), factors such as time, cooperation in research, ownership, a supportive work environment, coaching on inquiry-based working and access to resources influence teachers' engagement in inquiry-based working. Other studies have demonstrated the importance of school leaders in terms of encouraging inquiry-based working (Schenke 2015).…”
Section: Factors That Promote or Hinder Inquiry-based Workingmentioning
confidence: 99%
“…Where the learning culture of teachers is concerned, the term professional learning culture is used (Oberon et al, 2014). Only those organizations that encourage a true culture of learning among their members have the best chances to innovate (Cameron and Quinn, 2011; Heijboer et al, 2013), to obtain advantages over the competition (Baars-Van Moorsel, 2003; Watkins and Marsick, 1996; Yolles, 2009), to transform themselves by creating new knowledge (Schenke, 2015) and to survive disruptions in the long run (March, 1991; O’Reilly and Tushman, 2013). Exact definitions of learning culture, however, are scarce.…”
Section: Theoretical Contextmentioning
confidence: 99%
“…Onderzoekend werken in scholen is een thema waarnaar de laatste jaren diverse onderzoeken zijn gedaan. Bijvoorbeeld Schenke (2015) keek naar innovatieprojecten in voortgezet onderwijs en zag hoe weerbarstig samenwerking kan zijn, ook als de omstandigheden gunstig lijnen. Uiterwijk-Luijk (2017) keek hoe en onder welke condities onderzoekend werken door schoolleiders en leraren in het primair onderwijs vorm krijgt.…”
Section: Masteropgeleiden En Onderzoekend Werken In Vmbo En Mbounclassified